Parasite infection leads to widespread glucocorticoid hormone increases in vertebrate hosts: A meta‐analysis. Issue 2 (8th November 2019) - O'Dwyer, Katie; Dargent, Felipe; Forbes, Mark R.; Koprivnikar, Janet
Abstract: Parasites and pathogens (hereafter parasites) commonly challenge organisms, but the extent to which their infections are physiologically stressful to hosts remains unclear. Importantly, vertebrate hormones, glucocorticoids (GCs), have been reported to increase, decrease or show no alterations stemming from infections, challenging the generality of parasite‐associated GC responses and motivating a search for important moderator variables. We undertook the first meta‐analysis of changes in vertebrate GCs following experimental infection with parasites, extracting 146 effect sizes from 42 studies involving 32 host and 32 parasite species to test for general patterns of GC following infection, as well as the influence of moderators. Overall, infection increased GCs relative to preliminary or control levels when the single largest effect sizes from repeated measures studies were examined, suggesting that parasites of vertebrate hosts can be thought of generally as physiological stressors by elevating GCs. When all effect sizes were included along with the moderator of sampling time post‐infection (tPI), parasite infection still had a positive effect on host GCs. However, the strength of that effect did not relate consistently to tPI, illustrating temporal differences in GC changes during the course of infection among parasite taxa (e.g. arthropod vs. bacterial infections). Other moderator variables examined did not influence GC responses. Studies broadening the range of host and parasite taxa, and sampling during critical time windows, would aid in our understanding of variation in the host stress response and its consequences for fitness of both vertebrate hosts and their parasites. Abstract : While it is widely thought that parasitic infections raise levels of stress‐associated hormones, this study is the first to demonstrate that this holds true across many vertebrate hosts and parasites for glucocorticoid hormones. Infection generally causes glucocorticoid increases at some point, but patterns vary depending on the parasite or pathogen.